(3Jbhje GdCOhjI ajeG CTJgQ ef GdCYTGH hGdYbGbjQ hGdCZPjIs - (3EHQGgje Hf CHj SYjO Hf EHQGgje GdeZQHj GdYdGFj GdeJWHHs ((3YeQ Hf eMeO s)
(3ChdgG (B:s
(3Ef Chd eG GaJJM Hg GdNWGH hCLd eG GHJOF Hg GdcJGH (B: (3GdJYXje dPcQ Gddg HCSeGFg deG cGfJ GdCOhjI hGdCZPjI eGOI JMbjb UMI GdEfSGf s
(3BNQgG (B:s
(3jfJgi HPcQ GdCOhjI GdJi dgG CSeGf Ch KdGKI hZSG (B: (3gh GdHdM , PcQ ai MQa GdHGA ZdJGf (B: (3gh GdLOhGQ PcQ ai MQa GdLje s
(3GdeDda cGf MjkG SfI (B547(3g`s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B66 s
Keywords: (3GdWHs